Characterizing the Onset Potential Distribution of Pt/C Catalyst Deposition by a Total Internal Reflection Imaging Method. Issue 45 (5th October 2021) - Li, Fuying; Ma, Kaijie; Liu, Le; Xi, Jingyu; Qiu, Xinping
Abstract: A catalytic electrode with extraordinary performances for hydrogen evolution reaction (HER) should achieve a low onset potential of the bulk electrode, as well as its uniform distribution. Herein, a total internal reflection imaging (TIRi) method to characterize the onset potential distribution of the catalytic electrode surface is presented. When the potential scans toward negative in a linear sweep voltammetry, the equivalent refractive index of the electrolyte on the electrode surface will decrease due to H2 microbubbles generation, leading to the increase in optical intensity. Analysis of the relationship between the optical intensity and potential in each region results in the onset potential distribution. The TIRi method reveals poor uniformity and repeatability in the catalytic electrodes which are fabricated by depositing Pt/C catalysts on a porous carbon support with polymer binders (e.g., Nafion). Further electrochemical stability test also shows poor durability, whose HER onset potential deteriorates from the edge to the middle of these catalytic electrodes. The present TIRi method realizes direct visualization of the activity distribution on the bulk electrode surface, which provides a powerful tool for better fabrication and evaluation of large‐area HER electrodes in industrial energy devices. Abstract : The scalable and sustainable generation of hydrogen through hydrogen evolution reaction (HER) in water splitting requires large‐area catalytic electrodes with a uniform activity distribution. Considering traditional bulk electrochemical tests typically afford the average HER performances, a total internal reflection imaging method is presented to characterize the electrocatalytic activity distribution of HER bulk electrode surface by mapping the local onset potential.